1999
DOI: 10.1038/sj.jhh.1000761
|View full text |Cite
|
Sign up to set email alerts
|

Sodium–blood pressure interrelationship in pregnancy

Abstract: In non-pregnant individuals, a strong positive association of sodium intake with blood pressure has been established, but the relationship between sodium intake and blood pressure in human pregnancy remains obscure up to date. The aim of this prospective observational cohort study was to assess the relationship between urinary sodium excretion (as a measure for intake) and blood pressure from the early second trimester onwards throughout pregnancy. The study group consisted of 667 low-risk women with singleton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…These women were studied prospectively throughout pregnancy in two related cohort studies, originally designed to evaluate whether dietary sodium restriction has an effect on blood pressure in pregnancy [10,11]. The first study was conducted from 1990 to 1991 in the area of the Maria Hospital, a general teaching hospital in Tilburg, The Netherlands (Tilburg cohort).…”
Section: Patient Populationmentioning
confidence: 99%
“…These women were studied prospectively throughout pregnancy in two related cohort studies, originally designed to evaluate whether dietary sodium restriction has an effect on blood pressure in pregnancy [10,11]. The first study was conducted from 1990 to 1991 in the area of the Maria Hospital, a general teaching hospital in Tilburg, The Netherlands (Tilburg cohort).…”
Section: Patient Populationmentioning
confidence: 99%
“…A prospective study reported that, prior to 32 weeks gestation, no difference could be demonstrated in the association between urinary sodium excretion and arterial pressure in women who remained normotensive and those who became hypertensive. 186 The excretion of a sodium load does not differ significantly between non-pregnant and normotensive pregnant women in the second trimester, but in the third trimester, there is a tendency to sodium retention and expansion of plasma volume under these circumstances. 187 These authors reported that in a prospective study of salt loading in second trimester primigravidae, those who went on to develop GH did not handle a sodium load differently from those who remained normotensive.…”
Section: Renal Functionmentioning
confidence: 99%
“…Water balance is controlled by thirst and the secretion of ADH, which are regulated primarily by serum osmolality. In pregnancy the osmotic threshold for ADH release and thirst stimulus is reset down, 14,15 a process which has been interpreted to result from a baroreceptor stimulus from arterial Queensland Diabetes and Endocrine Centre, Mater Misericordiae Hospital, Brisbane, Australia underfilling overwhelming the osmostat. 16 Vasopressinase is released by placental trophoblasts in concentrations proportional to placental weight, so activity is higher in the third trimester or in multiple pregnancies.…”
Section: Renalmentioning
confidence: 99%